How can quantitative policy analysis inform the energy transition? The case of electrification - Vaishnav, Parth (Frontiers in Sustainable Energy Policy, 2023)
Quan'ta've analyses may aim to provide ac'onable answers to policy ques'ons and to generate tools or insights for decision-making. Given the deep uncertain'es involved in any realis'c reckoning of policy ques'ons, I argue that only the second of these goals is achievable. I illustrate this argument by considering analyses of how electrifica'on of an ac'vity changes the damages from the air pollu'on emissions that occur because of that ac'vity. The sources of uncertainty in such an analysis include the long life of the technologies being studied. Consequently, the structure and opera'on of the electricity grid might change because of the new technology and independent of it. Analysts must make subjec've choices about what to include in their analysis and what to exclude. For example, policies modeled in isola'on may in reality be bundled with other policies; interac'ons between technologies may be missed if the analysis focuses on only one technology; and certain benefits or costs may be neglected because they lie outside the scope of the analysis and the exper'se of the analyst. Quan'ta've policy analysis must aim to be part of the broader discussions in society that ul'mately determine what policies get implemented.